Focus Group Research in the Academic Library: An Overview of the Methodology - Weare, William H. (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
Through the use of focus groups, academic librarians can discover what students really think, feel, need, and want. Equipped with this knowledge, librarians will be better positioned to design and deliver effective programs, improve services, and shape the development of facilities to better meet the needs of current and future users. Concerned about the efficacy of various library programs and initiatives at Valparaiso University (Valparaiso, Indiana, USA), two public services librarians conducted a series of focus groups with undergraduate students to gain a better understanding of their perceptions of the library. This paper provides an overview of the focus group methodology employed in this study.